Correction of characteristics of high-voltage test transformer - Бржезицький, Володимир Олександрович; Гаран, Ярослав Олександрович (Technology audit and production reserves, 2015)
Dependence of performances of serial high-voltage testing transformer ИОМ-100/25 with a measuring winding from character of a loading is explored. Substantial growth of a high voltage measuring error by means of measuring winding ИОМ-100/25 is fixed at a capacitive load. The cause of a capacitive load effect on a measuring error of a high voltage for the given type of transformers and its analogues is defined – proportions of a leakage inductance of a measuring winding and all high-voltage winding do not coincide with the nominal division ratio for these windings, owing to design features of the given type of transformers. The procedure of the high voltage measuring error correction defined by means of measuring winding ИОМ-100/25 (or analogous transformers), by means of compensation of the inductive voltage drop on measuring winding by the additional capacitor which is switched on in succession with a measuring winding is offered. The results of the research can be used to upgrade the high voltage electrical testing laboratories.